The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1167/iovs.61.5.53
|View full text |Cite
|
Sign up to set email alerts
|

Defocus Incorporated Multiple Segments Spectacle Lenses Changed the Relative Peripheral Refraction: A 2-Year Randomized Clinical Trial

Abstract: Incorporated Multiple Segments spectacle lenses changed the relative peripheral refraction: a 2-year randomized clinical trial. Invest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 46 publications
(76 reference statements)
4
64
0
Order By: Relevance
“…Normally, the lenslets should be located in the periphery, and central vision should be aligned with the central clear zone. Studies have found that VA was not affected when looking through the central clear zone ( Lam et al, 2019 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, the lenslets should be located in the periphery, and central vision should be aligned with the central clear zone. Studies have found that VA was not affected when looking through the central clear zone ( Lam et al, 2019 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The geometry of the aspheric lenslets (1.12 mm in diameter) was calculated to generate a volume of myopic defocus ranging from 1.1 to 1.9 mm (HAL) and from 1.0 to 1.3 mm (SAL) in front of the retina at any eccentricity, serving as a myopia control signal. The lenslets (1.03 mm in diameter) of HC introduce myopic defocus at a plane in front of the retina by a relative positive power (+3.50 D) ( Lu et al, 2020 ; Zhang et al, 2020 ). The surface of the lens without lenslets provides distance correction.…”
Section: Methodsmentioning
confidence: 99%
“…This theory of the progression of myopia suggests that axial elongation is driven by peripheral retinal hyperopic defocus; in this sense, any hyperopic blur in the peripheral retina has been shown to conduct to axial length and myopia progression in animal and human studies. On the basis of this theory it has been considered that minimising the retinal peripheral hyperopic defocus or inducing peripheral myopic defocus with bifocal progressive addition spectacles (PAL), peripheral defocus ophthalmic lens [ 29 ] or with different designs of CLs could prevent myopic progression [ 19 ]. The mechanisms that support myopia control with CLs are also based on the change in retinal peripheral defocus [ 22 ].…”
Section: Current Treatment Options and Gapsmentioning
confidence: 99%
“…For patients with poor compliance with follow-up visits, there is no reason to believe that they can use antibiotics correctly when indicated and, considering the potential risk arising from non-compliance with treatment, they are probably not suitable candidates for ortho-k treatment. Currently, there are several novel non-contact lens myopia control modalities other than ortho-k, including specially designed spectacles [ 15 , 16 ] and low-concentration atropine [ 17 , 18 ], which could be considered when compliance is an issue for patients.…”
Section: Discussionmentioning
confidence: 99%